Penerapan Intelegensi Buatan Dengan Algoritma Negamax pada Aplikasi Permainan Deret Lima - Ridwanto Salmon; Imron Nugraha; Saharudin (Jurnal Bangkit Indonesia, 2017)
The development of technology is growing rapidly, including developments in the world of digital entertainment, in this case the development of computer-based games. Artificial intelligence is part of technological advancement itself that makes machines or computers able to do work like and as well as humans where computers can think like humans, in the world of computer games too, computers can think like humans in playing games. The five-line game that applies the development of computer-based digital game technology using artificial intelligence with the Negamax algorithm to form computers can play, thinking like humans in arranging five balls in a row horizontally, vertically, or diagonally where computers can beat humans in playing The fifth line game is a symmetrical type of game, which uses a checkerboard in its game. Players will arrange five white and black balls in a row either horizontally, vertically or diagonally on the game board. The player who can arrange the balls first wins the game.